Pengaruh Budaya Organisasi dan Kepemimpinan Transformasional terhadap Kinerja Karyawan dengan Motivasi Kerja sebagai Variabel Intervening pada PT.Cipta Kridatama Site KIM, Jambi - Tasya Tasya; Marta Widian Sari; AI Elis Karlinda (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of organizational culture and transformational leadership on employee performance with work motivation as an intervening variable at PT. Cipta Kridatama Site KIM, Jambi. This research uses a quantitative approach with a survey method, and data were collected using a questionnaire distributed to 70 employees as respondents. Data analysis was conducted using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach through SmartPLS version 3. The results show that organizational culture does not have a positive and significant effect on work motivation and employee performance. On the other hand, transformational leadership has a positive and significant effect on work motivation and employee performance. Furthermore, work motivation has a positive and significant effect on employee performance. Work motivation was not able to mediate the effect of organizational culture on performance, but it successfully mediated the effect of transformational leadership on employee performance. These findings indicate that the role of leaders in inspiring and supporting employees is crucial for improving organizational performance.